(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1997)
The objective of this work is to analyze the Miocene depositional units of the southern side of the Volterra Basin (Tuscany, Italy) utilizing outcrop and seismic data and to establish the major events that led to their formation. Four depositional units have been recognized: Unit 1 is characterized by marine sediments of late Serravallian-early Tortonian age; Unit 2 is characterized by fluvio-lacustrine and brackish deposits of late Tortonian-early Messinian age; Unit 3 is characterized by marine deposits of early Messinian age; Unit 4 is characterized by the lacustrine deposits ("Lago-mare" facies) of late Messinian age. The deposition of these four units is associated with an extensional tectonic regime that has been active in Tuscany since the late Tortonian. This regime generated half graben type structures in which deposition occurred. The recognized unconformities between the units are mainly related to uplift as a consequence of the extensional tectonic regime.